PENYEMPURNAAN AKHLAK DALAM HADIS SEBAGAI KERANGKA FILOSOFIS - Fauzi, Moh. Hasan; Abu Muslim; Bustanul Yuliani (Program Studi Ilmu Tasawuf Universitas Pangeran Diponegoro Nganjuk, Jawa Timur, 2026)
This study aimed to reconstruct the ḥadīth “innamā buʿithtu li-utammima makārim al-akhlāq” as a systematic philosophical foundation of Islamic education within contemporary educational discourse. The study employed a qualitative–philosophical approach through textual analysis of the ḥadīth, critical engagement with classical commentaries, and conceptual dialogue with Islamic and modern educational philosophy. Data were analyzed using ontological, epistemological, and axiological frameworks to uncover the educational structure embedded in the ḥadīth. The findings demonstrated that the ḥadīth on moral perfection functioned not merely as a normative moral statement but as a coherent conceptual framework of education. Ontologically, the ḥadīth positioned education as a holistic process of human formation oriented toward moral perfection. Epistemologically, the concept of utammima indicated an integration of revelation, reason, and experience as sources of moral knowledge. Axiologically, moral character was established as the ultimate aim of education, with cognitive and instrumental achievements serving as supportive means rather than final goals. The study concluded that the ḥadīth on moral perfection possessed strong theoretical potential to be repositioned from ethical rhetoric to a systematic foundation of Islamic educational philosophy. The novelty of this study lay in conceptualizing the ḥadīth as a philosophical framework that bridges Islamic transcendental values and contemporary educational theory beyond normative interpretation.